2022
DOI: 10.1038/s41467-022-35093-9
|View full text |Cite
|
Sign up to set email alerts
|

Discrete LAT condensates encode antigen information from single pMHC:TCR binding events

Abstract: LAT assembly into a two-dimensional protein condensate is a prominent feature of antigen discrimination by T cells. Here, we use single-molecule imaging techniques to resolve the spatial position and temporal duration of each pMHC:TCR molecular binding event while simultaneously monitoring LAT condensation at the membrane. An individual binding event is sufficient to trigger a LAT condensate, which is self-limiting, and neither its size nor lifetime is correlated with the duration of the originating pMHC:TCR b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 107 publications
6
37
0
Order By: Relevance
“…In an analogous manner to TCRs, both antigen density and pHLA dissociation rate from the 10LH CAR can contribute to our observation that HLA-A*23:01, which has approximately two orders of magnitude reduced binding to 10LH relative to HLA-A*24:02 (2.6 μM versus 11 nM K D ), shows potent CAR T cell killing of tumor cells ( 14 ), because both interactions show similar k d values by SPR (0.0085 s −1 versus 0.0022 s −1 ). These results allow us to establish a relationship between pHLA dissociation rate from the scFv—expressed as CAR dwell time—and CAR T cell activation, cytokine release, and cytotoxicity, established by previous studies focusing on both TCRs and CARs ( 28 30 ).…”
Section: Resultsmentioning
confidence: 54%
“…In an analogous manner to TCRs, both antigen density and pHLA dissociation rate from the 10LH CAR can contribute to our observation that HLA-A*23:01, which has approximately two orders of magnitude reduced binding to 10LH relative to HLA-A*24:02 (2.6 μM versus 11 nM K D ), shows potent CAR T cell killing of tumor cells ( 14 ), because both interactions show similar k d values by SPR (0.0085 s −1 versus 0.0022 s −1 ). These results allow us to establish a relationship between pHLA dissociation rate from the scFv—expressed as CAR dwell time—and CAR T cell activation, cytokine release, and cytotoxicity, established by previous studies focusing on both TCRs and CARs ( 28 30 ).…”
Section: Resultsmentioning
confidence: 54%
“…Finally, in single-cell molecule experiments, pMHC-bound TCRs give rise to pLAT clusters only in a fraction of cases (25-50%), even when they were bound for very long times 24 . This cap on TCR-induced clustering likely arises from feedback mechanisms which deactivate pMHC-bound TRCs over time.…”
Section: Simulated Lat Cluster Sizes and Dynamics Match Single-molecu...mentioning
confidence: 96%
“…Having shown that pLAT alone can undergo clustering in our model, we proceeded to ask whether pLAT can form clusters in response to TCR pMHC engagement and LAT phosphorylation. Single-molecule studies had previously shown that single TCRs can induce LAT clusters with a variable time delay after pMHC binding 24 . In these experiments TCRs are only tracked after they bind to a pMHC, and the peptides used are very high affinity.…”
Section: Individual Bound Tcrs Nucleate Signaling Condensates With a ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another important and emerging feature of signal transduction at the plasma membrane is the formation of membrane proximal, liquid‐liquid separated cytoplasmic condensates at the signaling sites. [ 7 ] In these condensates, proteins are highly concentrated and how this interface affects the diffusion of plasma membrane associated signaling molecules would be an interesting avenue to explore.…”
mentioning
confidence: 99%